15.5k views
2 votes
Solve for v

-(2/3)v-1=(7/2)v-(4/3)

User Aarti
by
6.3k points

2 Answers

6 votes

Answer:

v = 2/25

Explanation:

We have given the equation:

-(2/3)v-1=(7/2)v-(4/3)

We have to solve it for v.

-(2/3)v-1=(7/2)v-(4/3)

(7/2)v+(2/3)v = -1+(4/3)

Multiply both sides of equation by 6 we get,

21v+4v = -6+8

25v = +2

Multiplying both sides by 1/25 we get,

v = 2/25

v = 2/25 is the answer.

User SAFAD
by
6.1k points
0 votes

Answer:
v=(2)/(25)

Explanation:

To solve from v from the equation given in the problem you must apply the folowing proccedure:

- Add like terms:


-1+(4)/(3)=(7)/(2)v+(2)/(3)v\\\\ (1)/(3)=(25)/(6)v

- Mulitply bot sides of thee equation by 6 and then divide both sids by 25.

Therefore you obtain:


(1)/(3)=(25)/(6)v\\(6)/(3)=25v\\v=(2)/(25)

User Papa John
by
6.0k points